2015
DOI: 10.15621/ijphy/2015/v2i5/78227
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cyriax Physiotherapy Versus Eccentric Strengthening and Stretching Exercises in Chronic Lateral Epicondylitis Patients

Abstract: Background: Lateral Epicondylitis is the most common lesion of the elbow, affecting the tendinous origin of the wrist extensors. Although conservative treatment of this condition has been the subject of numerous studies, there is no agreement as to the most effective management strategy. Therefore, this study was designed to compare the efficacy of Cyriax physiotherapy Versus Eccentric Strengthening and Stretching exercises in reducing the pain and improving the grip strength and functional status of the affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…Sample size was sixty n=60 and they found that Cyriax treatment was significantly effective in improving pain and hand grip strength. 26 This study is similar to current study in treatment duration, measuring tools and in results. Bill Vicenzino et al find out the efficacy of Mulligan's MWM in pain relief and to correct positional fault not only in tennis elbow but also in all other musculoskeletal disorders.…”
Section: 24supporting
confidence: 87%
See 1 more Smart Citation
“…Sample size was sixty n=60 and they found that Cyriax treatment was significantly effective in improving pain and hand grip strength. 26 This study is similar to current study in treatment duration, measuring tools and in results. Bill Vicenzino et al find out the efficacy of Mulligan's MWM in pain relief and to correct positional fault not only in tennis elbow but also in all other musculoskeletal disorders.…”
Section: 24supporting
confidence: 87%
“…25 Two studies from past literature also showed improvement in pain by Cyriax approach and mulligan approach. 26,27 One study was conducted by Madhusmita Koch and his colleagues to find out the effectiveness of Cyriax and eccentric strengthening and stretching exercises. Sample size was sixty n=60 and they found that Cyriax treatment was significantly effective in improving pain and hand grip strength.…”
Section: 24mentioning
confidence: 99%